Perubahan Perilaku Konsumen Sebagai Dampak Kebijakan PPnBM di Surabaya Pada Tahun 2021 - Soegianto, Danny (Jurnal Etnik: Ekonomi-Teknik, 2022)
During the Covid-19 pandemic, the Indonesian economic sector experienced a significant decline, one of which was the car market. The strategy taken by the government to increase people's purchasing power, especially cars, to receive PPnBM relaxation starting in March 2021. This PPnBM relaxation aims to encourage the industry to move and boost car sales so that in some sectors things can return to normal. This study aims to determine changes in consumer behavior from the impact of PPnBM policies in terms of consumer behavior in Surabaya. This research was conducted using a qualitative method with a non-probability sampling technique, and also used in-depth interviews with resource persons who met the criteria determined by the author. Based on the results of the analysis of the author's in-depth interview with the resource person, it was found that there was a correlation between the answers given by the resource person and the theory used by the author as a reference in conducting this research